Assessment of Group a Streptococcus and Antimicrobial Resistance Pattern in School Going Children in Morang District, Nepal - Chaudhary, Kabita Kumari; Khanal, Hemanta; Singh, Ganesh Kumar; Chaudhary, Silak Ram; Sah, Om Prakash (Birat Journal of Health Sciences, 2020)
Introduction: Group A hemolytic Streptococcal infections has worldwide distribution among children and it poses an important problem globally. There is lack of baseline information regarding Group A hemolytic streptococci in school going children in the eastern part of Nepal.Objective: The study was conducted for assessing the carrier rate of Group A hemolytic streptococci in school going children in eastern part of Nepal.Methodology: This study was community based cross-sectional study. During the study of 9 months, a total of 518 patients (school-going children) from different school who were symptomatic as well as asymptomatic were enrolled. All samples were collected by rubbing quickly and thoroughly over either tonsils (or tonsillar fossa) and over the posterior wall of the pharynx using light pressure and were subjected to microbial analysis in the clinical Microbiology Laboratory. The specimens were inoculated immediately into Blood agar (BA) and MacConkey agar (MA) and were incubated at 37°C aerobically and were checked for growth after overnight incubation. The identification of bacterial isolates was carried out by Clinical and Laboratory Standards Institute (CLSI) guidelines with colonial morphology and staining reactions. Biochemical tests such as catalase, bacitracin sensitivity test (0.004 units) and Lancefield grouping (PastorexTM Strep) were performed. All the identified S. pyogenes isolates thus obtained were subjected to in vitro antibiotics sensitivity testing by using Kirby-Bauer disc- diffusion method as recommended by CLSI (2014).Results: During 9 months period total 518 throat swabs (303 male and 215 female)from school going children attending government and private school were collected after taking verbal consent and were cultured on blood agar and MacConkey agar.Streptococcus pyogenes was identified by using standard microbiological procedures. Antimicrobial susceptibility testing of the isolates was performed by Kirby Bauer disc diffusion method. Group A streptococci (GAS) was isolated from 28 (5.4%) school going children, of which 15 (5%) were male and 13 (7%) were female. There was no significant sex difference in colonization of GAS (p>0.05). Majority of cases were asymptomatic. In this study it was observed that the sensitive drugs for GAS were Penicillin and their deravatives (100%), Ciproflocaxin (100%) and Azithromycin (100%) followed by Erythromycin (75%) and Cotrimoxazole (71.4%) (Table 9,10).Conclusion: The present preliminary study provides the base-line information on the GAS carriage rate and resistance trend among healthy school children. The present study showed that Penicillin and its derivatives should be used to treat a case of GAS pharyngitis and Azithromycin for those who are allergic to Penicillin. The present study also showed that Staphylococcus aureus as an equally important agent of pharyngitis and hence throat swab culture should be requested for appropriate therapy.